Justice gone - Lombardi, N., Jr. (Winchester, UK ; Washington, USA : Roundfire Books, 2019)
When a homeless war veteran is beaten to death by the police, stormy protests ensue, engulfing a small New Jersey town. Soon after, three cops are gunned down. A multi-state manhunt is underway for a cop killer on the loose. And Dr. Tessa Thorpe, a veteran's counselor, is caught up in the chase. Donald Darfield, an African-American Iraqi war vet, war-time buddy of the beaten man, and one of Tessa's patients, is holed up in a mountain cabin. Tessa, acting on instinct, sets off to find him, but the swarm of law enforcement officers get there first, leading to Darfield's dramatic capture. Now, the only people separating him from the lethal needle of state justice are Tessa and ageing blind lawyer, Nathaniel Bodine. Can they untangle the web tightening around Darfield in time, when the press and the justice system are baying for revenge? Justice Gone is the first in a series of psychological thrillers involving Dr Tessa Thorpe, wrapped in the divisive issues of modern American society including police brutality and disenfranchised returning war veterans. N Lombardi Jr. is the author of compelling and heartfelt novel The Plain of Jars.
Keywords: Suspense fiction